Ketamine-Based Treatment of MDD: A Biologist’s Perspective - Li, Shupeng; Zhang, Yingli; Zhou, Qiang (Journal of Depression And Therapy, 2017)
Ketamine’s potential as a fast-acting reagent to treat MDD, especially treatment-resistant depression has caught much attention recently. Although much has been learned about the biological mechanisms underlying ketamine’s effect, there are a few critical issues remained to be resolved. This mini review will briefly discuss several controversial issues that warrant further studies, regarding the molecular, physiological, psychopharmacological, and behavioral effects of ketamine. Understand how ketamine works as an anti-depressant will open the door to better understanding of MDD and its treatment.
Keywords: Ketamine; depression; glutamate; NMDA receptor; psychosis